Application of magnetic multi-wall carbon nanotube composite into fermentative treatment process of ultrasonicated waste activated sludge. (June 2020) - Mostafa, Alsayed; Tolba, Aya; Gar Alalm, Mohamed; Fujii, Manabu; Afify, Hafez; Elsamadony, Mohamed
Graphical abstract: Highlights: Fe3 O4 -MWCNTs achieved better WAS conversion, to H2, than Fe3 O4 and MWCNTs. Fe3 O4 NPs could enrich hydrogenase, while MWCNTs raised sludge conductivity. Fe3 O4 NPs exhibited higher substrate degradation efficiency than MWCNTs. Because of released ROS, Fe3 O4 revealed sharper toxicity than MWCNTs. Fe3 O4 -MWCNTs showed low ROS likely due to limited reaction of restricted Fe3 O4 . Abstract: This study investigated the effect of supplementing nano-sized magnetite (Fe3 O4 NPs), multi-wall carbon nanotubes (MWCNTs) and Fe3 O4 -MWCNTs composite on bioconversion of waste activated sludge to hydrogen, in batch systems. Substrate degradation efficiency (SDE) increased from 28 ± 3.8 (control) to 49 ± 5.9, 46 ± 4.8 and 52 ± 6.3% at optimal doses of 200 (Fe3 O4 NPs), 300 (MWCNTs) and 200 mg/L (Fe3 O4 -MWCNTs), respectively. Based on dissolved iron and sludge conductivity measurements, superior SDE in Fe3 O4 and MWCNTs batches have been assigned to enhanced dissimilatory iron reduction (DIR) and high sludge conductivity, respectively. Combined impacts for sludge conductivity and DIR were revealed in Fe3 O4 -MWCNTs system. In 200 mg/L (Fe3 O4 -MWCNTs) batch, catalytic activities of hydrogenase, protease and α-amylase peaked to 596, 146 and 131% (relative to control), respectively; as well as, highest volumetric H2 production of 607 ± 59 mL/L was acquired. Performance deteriorations at high concentrations of nanoparticles were caused by cellular oxidative stress induced by generated reactive oxygen species.